Challenges to curing primary brain tumours - Aldape, Kenneth; Brindle, Kevin M.; Chesler, Louis; Chopra, Raj; Gajjar, Amar; Gilbert, Mark R.; Gottardo, Nicholas; Gutmann, David H.; Hargrave, Darren; Holland, Eric C.; Jones, David T. W.; Joyce, Johanna A.; et al. (Nature reviews. Clinical oncology, 2019)
Brain cancer encompasses a diverse range of complex malignancies, many of which are associated with a poor prognosis and require more effective treatments. In this Position Paper, an international panel of clinicians and laboratory-based scientists convened by Cancer Research UK identify and discuss seven challenges that must be overcome if we are to cure all patients with a brain tumour.
Gesehen am 10.02.2020